Prices versus Quantities for Common Pool Resources - Frank Jensen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2001)
In Weitzman (1974) the choice between price and quantity regulation under imperfect information is analysed. It is shown that the choice between the two regulatory instruments depends on the sign of the sum of the curvatures of the cost and benefit functions. If the marginal benefit function is steep and the marginal cost function is flat quantity regulation is preferred over price regulation, while price regulation is preferred over quantity regulation if the marginal benefit function is flat and the marginal cost function is steep. The results in Weitzman (1974) are sometimes quoted in studies of fisheries management. In this paper an analysis of conditions for generalising the Weitzman result to fisheries economics is presented. It is shown that the result can be generalised if the cost function is additively separable in stock size and catches. This leads to the conclusion that the results hold for a schooling fishery. However, for a search fishery the condition that the cost function must be additively separable is seldom fulfilled and quotation of the classical article is therefore not reasonable. A further result is that for a schooling fishery, taxes are likely to be preferred over individual transferable quotas in the case where there is imperfect information about costs. The reason is that the marginal cost function is likely to be steeper than the demand function. In the light of this result, the fact that individual quotas regulate over 55 fisheries while taxes regulate none is surprising.
Keywords: 330; Fisheries Management; Imperfect Information; Taxes; Individual Transferable Quotas; Fischereiressourcen; Fischereipolitik; Quotenregulierung